2023
DOI: 10.3390/nu15122791
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review on the Association between Night Eating Syndrome and Physical Health, Health-Related Quality of Life, Sleep and Weight Status in Adults

Abstract: Night eating syndrome (NES) is characterised by recurrent episodes of night eating, evident through excessive food consumption after the evening meal or eating after awakening from sleep, often associated with significant distress and/or impairment in functioning. This scoping review was conducted according to PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses for Scoping Reviews) guidelines. The search was conducted through the use of PubMed, Medline (OVID) and SCOPUS, to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…The patients with a BMI of greater than or equal to 50 kg/m 2 often have high prevalence of OSA, cardiac insufficiency, hypertension, diabetes 17 . So the surgeons were most concerned about respiratory and heart failure, extubation failure under anaesthesia, difficulty in surgical operation, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…The patients with a BMI of greater than or equal to 50 kg/m 2 often have high prevalence of OSA, cardiac insufficiency, hypertension, diabetes 17 . So the surgeons were most concerned about respiratory and heart failure, extubation failure under anaesthesia, difficulty in surgical operation, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…Research has revealed that more than half (55%) of individuals with obesity seeking bariatric surgery report NES symptoms [ 51 ]. Although a greater NES prevalence exists in patients with obesity (10.1–27%) [ 44 , 52 , 53 , 54 ], not all individuals with NES symptomatology are, in fact, obese [ 48 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. Furthermore, research using the NEQ has revealed a greater NES prevalence among patients with mental illness (25%) [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…As per Plano et al [ 78 ], several ED aspects appear to be mediated by the circadian system, including mood, meal timing, compulsive behavior and sleep quality. In particular, most patients suffering from NES tend to exhibit an evening chronotype, with greater insomnia disturbances, reported poor sleep [ 94 , 95 ], lower sleep efficacy [ 94 ] and sometimes even sleep apnea [ 58 ]. Due to these confluences, some researchers argue that it is not clear if NES consists of a psychiatric disorder, a sleep disorder, a delayed circadian eating rhythm or simply a metabolic condition with sleep and mental health aspects [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, individuals with NES often experience significant distress and/or impairments in normal functioning [ 3 , 4 , 6 ]. With a prevalence of 1.5% in the general population of the United States [ 9 ], NES creates a substantial burden to the healthcare system, detrimentally impacting quality of life and increasing morbidity [ 4 , 6 , 8 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, inconsistent evidence exists regarding the impact of NES on body mass index (BMI; kg/m 2 ), physical health and sleep [ 4 , 6 8 , 11 13 ]. Additionally, a majority of the research on NES has been conducted within clinical settings [ 14 16 ] or in adolescent populations [ 17 19 ].…”
Section: Introductionmentioning
confidence: 99%